Approach to the trust as internal good of Public Relations - Moscol Mogollón, Ronnie (2022)
This article presents the complex environment in which the Public Relations, are developed is needed noticing his practice from a systemic perspective where the organizations and publics interact and influence reciprocally, for this reason the decision making process will be ethic. With a strategy based on trust, respecting the man’s nature, it is focused on the construction, maintenance and defense of the organizations with his audiences strengthening the quality of the links that those uniting; finally, generating trust is the constant in the profession. This is translated on a good reputation that in the long term is always most profitable.